The developing role of Islamic banking and finance from local to global perspectives - Bisisu, Fu'ad Hamdi, 1943- (Bingley, U.K. : Emerald, 2014)
This volume is designed to present a conceptual and practical illustration for the contemporary developing role of Islamic banking and finance components including Islamic banking, Non Islamic banking (Takaful and Financial Markets Tools and Products) with stronger focus directed to the regulatory aspects, country, regional case studies and International Financial Crisis impacts.Consequently this volume defines how public policies, governance, legal framework and field studies' lessons can help decision makers to identify the major factors that may shape the attitude of both Islamic Financial Institutions and customers towards safe and sound services and through defining main determinants for successful, strategic inclusion of the Islamic Financial System into real sustained development nationally, regionally and internationally.
Central banks' role in shaping the future of Islamic banking / Fouad H. Beseiso -- Shari'ah govenance applicable to Islamic banks in Malaysia : effect of Islamic Financial Services Act 2013 / Aishath Muneeza -- The impact of the international financial crisis on the performance of Islamic banks in MENA countries / Hajer Zarrouk -- Approach to the integration of Takaful Insurance in the Algerian market / Nesrine Bouzaher, Okba Necira, Sabrina Kerdoudi -- Challenges and opportunities for development of Islamic stockbroking in Malaysia / Mohammad Mahbubi Ali -- The opportunity for implementing Islamic project financing to the Indonesian infrastructure development / Ayomi Dita Rarasati, Bambang Trigunarsyah, Eric Too -- Islamic banks' mergers and acquisitions : impacts on performance and financial crisis in the U.K / Tarek Kandil, Dababrata Chowdhury -- Attitude of Muslims and Non-Muslims towards Islamic banking : an exploratory study in India / Mohammad Faisal, Asif Akhtar, Asad Rehman -- Strategic requirements to implement the privatisation program in Iran / Mohammad Dolatabadi, Lotfollah Forouzandeh.
Includes indexes.
Print version record
Keywords: Business & Economics -- International -- Economics; Banking; Finance; Economics, finance, business & management; Banks and banking -- Religious aspects -- Islam; Banks and banking -- Islamic countries; Finance -- Islamic countries; Finance -- Religious aspects -- Islam